Designing a Community of Inquiry in Online Courses - Fiock, Holly S. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
This article describes a practical approach for implementing instructional strategies in order to build a Community of Inquiry (CoI) into an online course. Online community building has positive effects on the quality of student learning, increases student engagement, and encourages motivation of students in online courses. The CoI is a theoretical framework focusing on facilitating meaningful learning experiences through three presences: cognitive presence, social presence, and teaching presence. This article will introduce the CoI framework by way of literature review focusing on CoI instructional strategies. Using Sorensen and Baylen’s (2009) seven principles of good practice, the author will structure CoI instructional activities into presence categories for practitioner use.